'A long, narrow and uphill road': The representation of Turkey–EEC/EU relations in the Turkish newspapers Cumhuriyet and Hürriyet (1959–2019). (December 2021) - Atay, Ayça Demet
Turkey's membership process to the European Union has been a 'long, narrow and uphill road', as former Turkish Prime Minister, and later President, Turgut Özal once stated. This study analyses the representation of the European Union–Turkey negotiation process in the Turkish newspapers Cumhuriyet and Hürriyet from 1959 to 2019 with the aim of understanding the changing meaning of 'Europe' and the 'European Union' in Turkish news discourse. There is comprehensive literature on the representation of Turkey's membership process in the European press. This article aims to contribute to the field by assessing the representation of the same process from a different angle. For this purpose, Cumhuriyet and Hürriyet newspapers' front page coverage of selected 10 key dates in the European Union–Turkey relations is analysed through critical discourse analysis.